10‐year trends of educational differences in long sickness absence due to mental disorders. Issue 4 (20th July 2017) - Sumanen, Hilla; Pietiläinen, Olli; Lahelma, Eero; Rahkonen, Ossi
Abstract : Objectives: Mental disorders are a key cause of sickness absence (SA) and challenge prolonging working careers. Thus, evidence on the development of SA trends is needed. In this study, educational differences in long SAs due to mental disorders were examined in two age groups among employees of the City of Helsinki from 2004 to 2013. Methods: All permanently and temporarily employed staff aged 18‐34 and 35‐49 were included in the analyses (n= 27800 per year). SA spells of ≥14 days due to mental disorders were examined annually. Education was classified to higher and lower levels. Joinpoint regression was used to identify major turning points in SA trends. Results: Joinpoint regression models showed that lower educated groups had more long SAs spells due to mental disorders than those groups with higher education. SA trends decreased during the study period in all studied age and educational groups. Lower educated age groups had similar SA trends. Younger employees with higher education had the fewest SAs. Conclusions: A clear educational gradient was found in long SAs due to mental disorders during the study period. SA trends decreased from 2004 to 2013.